Long-Term Mortality After Osteoporotic Hip Fracture in Chiang Mai, Thailand - Tanawat Vaseenon (2018)
The purpose of the study was to investigate 10-yr mortality and associated factors after osteoporotic hip fracture. A prospective cohort study of mortality and associated factors was carried out in patients who sustained hip fracture and were admitted to Chiang Mai University Hospital from 1998 through 2003. Eligibility criteria were defined as age over 50 yr, hip fracture caused by simple fall, and Singh index of 3 or less.Mortality rates at 3, 6, 12, 24, 36, 60, 96, and 120 mo were 10%, 14%, 18%, 27%, 32%, 45%, 55%, and 68%, respectively. One-year mortality rates were 31% in males and 16% in females. The median survival time was 6 yr. Ten-year mortality was 68%. Factors correlated with higher mortality were male gender, age greater than 70 yr, and nonoperative treatment. Mortality after osteoporotic hip fracture in Thais was extremely high, especially in the first year. It was about 8 times higher than that in the age-adjusted general population. © 2010 The International Society for Clinical Densitometry.